(untitled) (Global Journal of Human-Social Science, 2018)
The paper will unveil how both R K Narayan and Wole Soyinka contributed much to establish peace in their respective countries through their literary works They have engaged themselves in a journey to protect traditionalism and the practices of their cultures from any kind of foreign intrusion Almost all their literary works bear the testimony to their peace-making efforts However amid them The Guide by R K Narayan and The Lion and the Jewel by Wole Soyinka make it clear that both writers have prioritized traditionalism over modernity This research discovers how the characters of the above-mentioned texts engage themselves in different deeds to find out the auspicious of traditionalism and the negative aspects of modernity and how they succeed in doing so At last the paper will bring out how both R K Narayan and Wole Soyinka have emerged as peace-makers through their literary contributions